Why dynamic capacity influences the quality of management accounting Information systems in the public sector? - Dian Wahyuningsih; Dio Caisar Darma; R. Ayke Nuraliaty; Jati Kasuma; Tănase Tasenţe; Siti Maria; Denis Ushakov; Sriwardani (International Journal of Psychosocial Rehabilitation, 2020)
The effectiveness of management accounting systems is also influenced by the dynamic capabilities of companies, where changing conditions and environments require changing management accounting information systems caused by sociological, technological, economic, and political factors. Thus, the pattern of organizational action will not involve the simplification, selectivity, and ties attached to each type of strategic action. Internal, external environment that is always changing will affect the management of accounting systems and organizational goals. The public sector with the existence of new public management will require dynamic capacity which will ultimately affect management accounting information systems. This study discusses the dynamic capacity carried out in the public sector to influence management accounting information systems. This study uses the literature review method to examine a variety of literature relating to dynamic capacity and management accounting information systems in the public sector. The results of this study found a dynamic need (government local, state, and local enterprises) for the quality of management accounting information systems in the public sector. Contribution/ Originality: This study will have dynamic capacity in the public good scores in institutions of government local, state, and local enterprises still requires a piece of system information are better able to follow the dynamic environment.